The Unicorn Mouse: Cranial Lipoma in a B6.Cg Mouse - Duncan, Taylor A.; Helke, Kristi L. (Brazilian Journal of Veterinary Pathology, 2022)
Intracranial lipomas, also called intracranial lipomatous hamartomas, have been reported in some strains of research mice, but are rare in C57BL6 strains. It is presumed based on current publications that this is the first report of an intracranial lipoma in a mouse with this genetic change (B6.Cg-Cnpy2tm1.2 Zhli Alb-Cre). Grossly, a fur-covered, soft, cylindrical, exophytic mass on the dorsal midline of the cranium was evident. Upon dissection, a soft, white, tubular structure extended through a 1mm defect in the sagittal suture of the skull to the deep surface of the hypodermis. Histologically, the mass consisted of well demarcated proliferation of mature white adipocytes, each containing one large fat droplet. The mass extended from the cerebrum at the level just caudal to the hippocampus in the third ventricle, between the superior colliculus and the caudal portion of the retrosplenial area and through the sagittal suture to the hypodermis and was surrounded by normal brain tissue.